Assessing alcohol-related beliefs using pictographic representations: a systematic approach to the development and validation of the revised alcohol expectancy task. (4th May 2022) - Monk, R. L.; Leather, J.; Qureshi, A. W.; Cook, M.; Labhart, F.; Kuntsche, E.; Heim, D
Abstract: Aim: To systematically develop and test stimuli for inclusion within the revised Alcohol Expectancy Task (rAET)-a pictographic assessment of alcohol-related beliefs.Using a UK adult sample of regular social drinkers, this paper documents the (1) selection (2)development and (3)testing of stimuli, along with (4)initial validation of the rAET. Method: A hierarchy of common alcoholic beverages was established, along with a consensus regarding beverage presentation format.A professional artist iteratively developed pictographs of characters exhibiting different emotions in everyday scenarios and specialised photography of beverages was undertaken. Accurate identification/recognition of these stimuli was then established using a response box, whereby participants indicated which word (from eight) matched the onscreen images presented.Finally, developed stimuli were included within the rAET. Results: Informing stimuli development and selection, wine, beer and vodka were the most common alcoholic beverages that participants reported consuming, with a preference for photographic representations.Inverse efficiency scores (based on accuracy and reaction time) suggested some variability in the recognition of certain beverage types and emotional stimuli, highlighting which stimuli may be best for inclusion in the rAET. Confirmatory factorial analyses of rAET responses suggests it has good construct validity. Conclusion: Maximising the transparency of stimuli selection, development and assessment provides a solid basis for systematic and valid scenario-based assessments of alcohol-related beliefs.